Risk analysis of machine maintenance using Markov chains - Gulati, Yuvraj Singh. (2013)
Maintenance and risk management are important issues in any manufacturing company. In order to keep equipment running efficiently and reduce maintenance cost for better profit margin, manufacturing plants have always been seeking a effective way to replace Corrective Maintenances (CM) that occur after unscheduled downtimes with more cost-effective Predictive Maintenance (PdM).